Costs of acquiring phosphorus by vascular land plants: patterns and implications for plant coexistence - Raven, John A.; Lambers, Hans; Smith, Sally E.; Westoby, Mark (The New phytologist, 2018)
We compare carbon (and hence energy) costs of the different modes of phosphorus (P) acquisition by vascular land plants. Phosphorus-acquisition modes are considered to be mechanisms of plants together with their root symbionts and structures such as cluster roots involved in mobilising or absorbing P. Phosphorus sources considered are soluble and insoluble inorganic and organic pools. Costs include operating the P-acquisition mechanisms, and resource requirements to construct and maintain them. For most modes, costs increase as the relevant soil P concentration declines. Costs can thus be divided into a component incurred irrespective of soil Pconcentration, and a component describinghowquickly costs increase as the soil P concentration declines. Differences in sensitivity of costs to soil P concentration arise mainly from how economically mycorrhizal fungal hyphae or roots that explore the soil volume are constructed, and from costs of exudates that hydrolyse or mobilise insoluble P forms. In general, modes of acquisition requiring least carbon at high soil P concentrations experience a steeper increase in costs as soil P concentrations decline. The relationships between costs and concentrations suggest some reasons why different modes coexist, and why the mixture of acquisition modes differs between sites.